Automated News Categorization using Machine Learning methods - Suleymanov, U.; Rustamov, S. (IOP Publishing, 2018)
Being one of the most linguistically rich languages, Azerbaijani has been researched less in the context of natural language processing area. The text corpus created from Azerbaijani news articles is designed to apply supervised machine learning approaches for the case of automatic news labeling. Chi-squared test and LASSO methods have been implemented for feature selection and pre-processing. The application of supervised machine learning approaches to the text corpus allowed us to compare the performance results of well-established supervised machine learning approaches in the domain of Azerbaijani language.
Keywords: Machine learning.; Artificial intelligence.; Data processing.